The role of serum albumin and albumin-related nutritional indices in predicting post-stroke cognitive impairment: a systematic review and meta-analysis - Yan-qiu Wang; Xia He; Xia-lian Huang; Fu-li Qin; Feng-le Mao; Yue-ming Cheng; Xiao-xue Zeng; Ying-ying Yang; Ming-xi Xu (Frontiers in Neurology)
BackgroundThe role of serum albumin levels and albumin-related nutritional indices in the prediction of cognitive impairment after stroke has not reached a uniform conclusion.MethodsThis study was prospectively registered in PROSPERO (CRD420251012150) and followed the PRISMA guidelines. We systematically searched six databases with a time frame from the date of database establishment to March 29, 2025. Literature selection and data collection were conducted by two researchers. Assessment of literature quality was performed according to the Newcastle-Ottawa Scale (NOS). Weighted mean difference (WMD) with 95% confidence intervals (CIs) was used to express pooled effect sizes. The chi-square (χ2) test (Cochran’s Q) and index of inconsistency (I2) were used to detect heterogeneity.ResultsA total of 9 studies involving 2,332 stroke patients were included in this meta-analysis. The results of this study showed that serum albumin levels (WMD: −3.85; 95% CI: −5.61, −2.09; p < 0.0001), Geriatric nutritional risk index (GNRI) (WMD: −2.68; 95% CI: −4.97, −0.39; p = 0.02), and HALP (hemoglobin, albumin, lymphocyte, and platelet) scores (WMD: −10.74; 95% CI: −19.98, −1.50; p = 0.02)were significantly lower in the post-stroke cognitive impairment (PSCI) compared to the post-stroke non-cognitive impairment (PSNCI).ConclusionDecreased serum albumin levels and albumin-related nutritional indices (GNRI and HALP scores) have a strong correlation with PSCI, which may become important indicators for early prediction of the development of PSCI.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#recordDetails, identifier, CRD420251012150.